Unraveling the Motivational Threads of Content Creators Embracing Mud Bath Content on TikTok - Sangadji, Suwandi S.; Wisnujati, Nughraini Susantinah (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2023)
Mud bathing through the TikTok platform has been a trend in Indonesia for the past few years. The purpose of this study is to determine the motivation of content creators to create live mud bath content through the TikTok platform. The method used in this study is a quantitative method with a descriptive approach based on frequency distribution. Determination of the number of samples using the Lemeshow formula so that a sample of 96 respondents who were the subjects of the study was obtained. The results of this study show that the motivation of content creators in creating mud bath content is to make money through online begging techniques, such as choosing elderly actors to do live mud baths and asking for gifts from the audience. The behavior of content creators is seen as a form of exploitation of the elderly with motives begging online. The implications of this research are that social media platforms need to take action to prevent content that is exploitative and harmful to others from being posted on their platforms. This can be done by tightening rules and regulations for creating and posting content and supervising and removing content that violates these rules.